The Concept “Semantic Invariant" as a Cognitive Term - S. A. Pesina (Дискурс)
Introduction. The purpose of the paper is to prove the semantic integrity of the meanings of polysemous words based on the use of the concepts “semantic network“ and “lexical invariant“. The relevance of this study lies in the lack of sufficient support of semantic integrity of lexemes, since there are contradictory linguistic data in favor of the so-called list theory of word representation in the mental lexicon. We put forward the hypothesis of network structuring of word meanings based on the “lexical invariant“, understood as a set of dominant basic semantic components, which underlie contextual meanings in one of their configurations. We pointed out the characteristic features and advantages of the network model of polysemous words as an open system capable of building an unlimited number of connections. The study is also concerned with the determination of the way the meanings are mapped in the semantic space of the lexicon by means of revealing the content of the semantic structures of the polysemous words.Methodology and sources. The paper presents an empirical invariant-component method of analyzing a polysemous word “key“.Results and discussion. The main results of the study indicate that there are numerous interconnected semantic networks of polysemous words in the lexicon. They function as multi-level configurations of meanings, which are cemented by dominant invariant meanings. Invariant meanings are eventually formed as a result of multiple use of all metaphorical meanings clusters, which allow native speakers to effectively navigate in the surrounding language environment.Conclusion. The results of our study have proved the idea that native speakers do not need detailed information (numerous semantic components) to interpret this or that meaning. The number of components they use in everyday communication is limited but sufficient for general understanding of the words and texts contents. The research results enabled us to draw a conclusion that in order to preserve the semantic integrity of a word structure, the number of meanings must remain within the limits of the invariant semantic components. The invariant lexical components form clusters of integral and differential types that combined in different configurations form a word desired meaning.